Coordinated changes in the expression of Wnt pathway genes following human and rat peripheral nerve injury. - Arie C van Vliet; Jinhui Lee; Marlijn van der Poel; Matthew R J Mason; Jasprina N Noordermeer; Lee G Fradkin; Martijn R Tannemaat; Martijn J A Malessy; Joost Verhaagen; Fred De Winter (PLoS ONE)
A human neuroma-in continuity (NIC), formed following a peripheral nerve lesion, impedes functional recovery. The molecular mechanisms that underlie the formation of a NIC are poorly understood. Here we show that the expression of multiple genes of the Wnt family, including Wnt5a, is changed in NIC tissue from patients that underwent reconstructive surgery. The role of Wnt ligands in NIC pathology and nerve regeneration is of interest because Wnt ligands are implicated in tissue regeneration, fibrosis, axon repulsion and guidance. The observations in NIC prompted us to investigate the expression of Wnt ligands in the injured rat sciatic nerve and in the dorsal root ganglia (DRG). In the injured nerve, four gene clusters were identified with temporal expression profiles corresponding to particular phases of the regeneration process. In the DRG up- and down regulation of certain Wnt receptors suggests that nerve injury has an impact on the responsiveness of injured sensory neurons to Wnt ligands in the nerve. Immunohistochemistry showed that Schwann cells in the NIC and in the injured nerve are the source of Wnt5a, whereas the Wnt5a receptor Ryk is expressed by axons traversing the NIC. Taken together, these observations suggest a central role for Wnt signalling in peripheral nerve regeneration.